Comparison of the Effectiveness Between Kuresif Audiovisual Media with Flipchart Media on Increasing Knowledge and Attitudes of 0-24 Month Invant Underweight’s Mother about Complementary Feeding - Suminar, Ratna; Setiawan, Henri; Suardi, Achmad; Komalaningsih , Sri; Garna , Herry; Wijayanegara , Hidayat; Sutisna , Ma'mun (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This research aims to compare the effectiveness between Kuresif audiovisual media and Flip Sheet Media in improving mothers' knowledge and attitudes. Methods: This type of research is a quasi-experiment with a pretest posttest control group design based on the total sampling technique. The research was conducted during August-September 2021. The sample consisted of 102 control groups and 102 intervention groups. Statistical analysis using the Wilcoxon test with questionaire. which aims to determine the effect of applying flip-sheet media and Kuresif audiovisual media on mothers' knowledge and attitudes in providing appropriate complementary feeding. Results: The results showed that in the flipchart media group there was an average increase in knowledge of 4,3% from 11,8% to 16,1%. Mothers' attitudes experienced an average increase of 20,9% from 56,8% to 77,7%. Meanwhile, in the kuresif audiovisual media group the average increase in knowledge was 6,9% from 12,4% to 19,3% and attitudes experienced an average increase of 33,4% from 59,1% to 94,5% with p=0,00. Conclusions: Kuresif audiovisual media is the most effective in increasing mothers' knowledge and attitudes compared with flipchart media. Indonesia is still facing nutritional problems that have a serious impact on the quality of human resources. Mother's lack of knowledge is one of the causes of improper nutritional intake. One way to accelerate efforts to break the cycle of nutritional problems is to increase mother's knowledge through counseling using flipchart media. Based on the evaluation carried out, the flipchart media has not shown an increase in the knowledge and attitudes of mothers regarding complementary feeding. Innovation is needed from counseling media in order to increase mother's knowledge and attitudes.